Legal Issues Against the Enforcement of Court Determination Granting Objections of Parties in Good Faith - Andriawan, Hilman; Ali, Mahrus (Jurnal Ius Constituendum, 2024)
The purpose of this research is to investigate the legal framework allowing the finance minister to enforce a court decision that approves a good faith third-party objection request, as well as to explore the legal implications and recourse if the finance minister fails to implement the court decision. This study is prompted by Supreme Court Regulation Number 2 of 2022, which elaborates on Article 19 of Law No. 31 of 1999. The significance of this research lies in providing legal certainty regarding the enforcement of court decisions granting good faith third-party objection requests. The research employs the normative legal research method and offers a new perspective by examining the implementation phase of objection application settlements. The findings indicate the Perma No. 2 of 2022 cannot be enforced without a regulation as a legal basis for the finance minister to govern the procedures for executing court decisions granting objections. Furthermore, the prohibition of state property confiscation leaves good faith third parties without legal protection, as there is no certainty about the legal consequences should the finance minister fail to implement the stipulation or court decision granting the objection of the good faith third party, and there are no available remedies for the Good Faith Third Party. Such Perma can not be effectively enforced without technical regulation on the procedure to execute the court verdict. Hence, it is recommended that the ministry of Finance needs to issue regulations concerning the execution of court verdicts providing legal certainty and protection for good faith third parties.